Examining the role of religion, spirituality and well-being on adults from divorced and non-divorced parents - Walker, Anthony B. (Kansas State University, 2008)
The purpose of this thesis was to examine the well-being of adults from divorced and non-divorced family backgrounds. The thrust of this thesis was to examine if and how adult well-being is influenced by family background factors, specifically support, safety, religiosity and spirituality. Data for this analysis come from the National Survey of the Moral and Spiritual Lives of Children of Divorce, a nationally representative sample of 1,510 adults ages 18-35, evenly divided by either divorced or non-divorced backgrounds. Using Social Learning and Social Exchange Theories, a path model was created to inform and guide this investigation. Bivariate and multivariate analyses were used to identify similarities or differences within and between groups and test hypotheses. Results indicate that adults from divorced homes, lower in spirituality and higher in religiosity experience lower well-being than adults from non-divorced homes, those with higher spirituality or lower religiosity. Childhood religiosity was not related to adult well-being for those from a divorced background. However, childhood religiosity demonstrated a positive relationship with adult well-being for adults from non-divorced backgrounds. The path model uncovered that, among other variables, income and family support were important predictors of well-being across groups. For the divorce group, education appears to be uniquely salient, while spirituality is more influential for the non-divorce group.
Keywords: religiosity; spirituality; religion; effects of divorce; adult well-being; Psychology, Social (0451); Sociology, Individual and Family Studies (0628)